Teaching Unheard Voices: Students At-Risk in Mathematics - Kajander, Ann; Zuke, Carly; Walton, Gerald (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
To examine the mathematics classroom experiences of students considered to be “at-risk,” we conducted case studies of four students in grades 7, 8, and 9 in North- western Ontario. The case studies revealed that their mathematics classes offered few opportunities for active, engaging learning or activities that students experienced as being relevant. Their teachers, who generally used traditional practices, seemed re- luctant or unable to adopt reform-based teaching methodologies. Based on the diver- sity of the observed students’ characteristics and learning needs, and the challenges these impose on classroom dynamics, we suggest earlier intervention for at-risk stu- dents as well as more substantial professional development for teachers. Key words: mathematics learning, mathematics education, classroom environments Afin d’analyser durant les cours de mathématiques les expériences d’élèves jugés à risque, les auteurs ont effectué des études de cas portant sur quatre élèves en 7e, 8e et 9e années dans le nord-ouest de l’Ontario. Ces études de cas ont révélé que leurs cours de mathématiques leur offraient peu d’occasions d’apprentissage actif ou d’activités pertinentes que les élèves pouvaient trouver intéressantes. Leurs enseig- nants, qui en règle générale utilisaient des méthodes pédagogiques traditionnelles, semblaient peu enclins ou incapables d’adopter des méthodes dérivant de la réforme. Compte tenu de la diversité des caractéristiques et des besoins des élèves observés quant à l’apprentissage et des défis que ceux-ci imposent à la dynamique de la classe, les auteurs suggèrent une intervention plus précoce auprès des élèves à risque ainsi que des activités de perfectionnement professionnel plus systématiques pour les enseignants. Mots clés : apprentissage des mathématiques, cours de mathématiques, prestation en classe